Product Values in the Digital Era and the Quest for Sustainable Competitive Advantage: A Bibliometric Mapping of Trends - Andriyansah, Andriyansah; Saputra, Nika (International Review of Management and Marketing, 2025)
Digital transformation is reshaping how organizations create product value and sustain competitive advantage, with technologies like Artificial Intelligence (AI), the Internet of Things (IoT), and blockchain playing a pivotal role. However, few studies integrate the concepts of product value and competitive advantage within a digital framework. This study uses a bibliometric approach aligned with PRISMA guidelines to explore shifts in academic discussions on product value and sustainable competitive positioning in the digital age. Data from the Scopus database (2014-2024) were analyzed using VOSviewer and Biblioshiny R software to identify key research themes and trends. Findings reveal a gap in research that holistically addresses product value dimensions, even though digital technologies have significant impacts. Sustainability is a key theme, yet its integration with digital technologies for sustainable product development is underexplored. This study highlights the need for greater integration of digital technologies and sustainability principles to enhance product value and ensure long-term competitive advantage. It contributes to the field by offering a bibliometric overview of current research trajectories and suggesting future research directions.